Anaphylactic reaction associated with Ranitidine in a patient with acute pancreatitis: a case report - Rethnam, Ulfin (BioMed Central, 2007)
Ranitidine is a widely used drug and is known to be well tolerated. This case report illustrates a severe anaphylactic reaction after a single intravenous dose of 50 mgs of ranitidine and highlights this unusual but life threatening adverse reaction. A 56 year old female with acute pancreatitis and a known allergy to metronidazole and buscopan developed an anaphylaxis few minutes following the injection of ranitidine for epigastric discomfort. She went on to develop anaphylactic shock and a cardiorespiratory arrest. She was managed with adrenaline, hydrocortisone and ventilatory support following which she had a full recovery. Awareness of this rare but life threatening adverse reaction to a commonly used drug can avoid being caught unaware.